2008
DOI: 10.1016/j.chemphyslip.2008.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The binary phase behavior of 1,3-dimyristoyl-2-stearoyl-sn-glycerol and 1,2-dimyristoyl-3-stearoyl-sn-glycerol

Abstract: The binary phase behavior of pure 1,3-dimyristoyl-2-stearoyl-sn-glycerol (MSM) and 1,2-dimyristoyl-3-stearoyl-sn-glycerol (MMS) was investigated in terms of polymorphism, melting and crystallization behavior, SFC, hardness and microstructure. Samples were crystallized at cooling rates of 3.0 and 0.1 degrees C/min. The asymmetric TAG demonstrated lower melting and crystallization points at both cooling rates. All samples crystallized in the beta' polymorph when cooled at 0.1 degrees C/min and in the alpha polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…(3) for each eutectic and a non-ideality of mixing parameter r for each branch ( Table 1). The calculated r-values are comparable to published values for binary lipid systems [18,19,22].…”
Section: Thermodynamic Analysis Of the Liquidus Linesupporting
confidence: 83%
“…(3) for each eutectic and a non-ideality of mixing parameter r for each branch ( Table 1). The calculated r-values are comparable to published values for binary lipid systems [18,19,22].…”
Section: Thermodynamic Analysis Of the Liquidus Linesupporting
confidence: 83%
“…Several studies can be found on the phase behavior of binary mixtures of TAGs, with a focus on molecular compound formation [9,13,[19][20][21]. It has been shown that, at carefully measured ratios (usually 1:1), it is possible to make pure binary mixtures of TAGs with synergistic properties such as solid fat content greater than either TAG in the mixture would exhibit alone [2,8,20,[22][23][24]. Most of the work in the field of molecular compound formation in binary fat systems to date has delved into the behavior of two-component mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…In the temperature‐molar fraction phase diagrams, simulation for the phase boundaries and evaluation for the miscibility between the compositions were conducted through a thermodynamic model, which was derived from the Hildebrand equation combined with the Bragg‐William approximation for non‐ideal blending. This model was also commonly applied to investigate the lipid mixtures .…”
Section: Methodsmentioning
confidence: 99%